Feminist humour? a critical analysis of Michaela Coel's Chewing Gum and Hannah Gadsby's Nanette - Perold, Jana (Stellenbosch : Stellenbosch University, 2024)
Thesis MA (VA)--Stellenbosch University, 2024.